Peran Strategis Experiential Marketing dalam Membangun Kepuasan dan Loyalitas Wisatawan Domestik - Nugraha, Lalu Maulana; Surata, I Ketut; Rucika, Nyoman Gde Dewa (LPPM Institut Pendidikan Nusantara Global, 2025)
This study explores the strategic role of experiential marketing in enhancing tourist satisfaction and attitudinal loyalty among domestic tourists in West Lombok, Indonesia. As tourism competition increasingly emphasizes emotional engagement and personal experiences, understanding how these experiences translate into loyalty is essential. The research employed a quantitative method using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze data from 130 respondents who had visited tourist destinations in West Lombok. The findings indicate that experiential marketing significantly and positively impacts tourist satisfaction and attitudinal loyalty. The marketing dimensions of sense, feel, think, act, and relate, as conceptualized in experiential marketing theory, are shown to meaningfully contribute to positive visitor perceptions. Specifically, the sense dimension (feeling safe and comfortable) received the highest ratings, reflecting its critical role in visitor experience. Moreover, tourist satisfaction mediated the relationship between experiential marketing and attitudinal loyalty, confirming a partial mediation effect. This means that while experiential marketing directly influences loyalty, its impact is strengthened when tourists also feel satisfied with their overall experience. The results also demonstrate that attitudinal loyalty, such as the intention to revisit and willingness to recommend destinations, can be effectively nurtured through high-quality, emotionally engaging experiences. In conclusion, this research supports the idea that a strategically designed experiential marketing approach is essential in developing competitive and sustainable tourism destinations. Tourism stakeholders are encouraged to integrate sensory, emotional, and cognitive elements into their services to strengthen both satisfaction and long-term loyalty.